Efficient evolutionary particle swarm optimization approach for nonconvex economic load dispatch problem - Abdullah, M.N.; Rahim, N.A.; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Illias, Hazlee Azil; Jamian, J.J. (Zagadnienie ekonomicznie uzasadnionego określenia wytwarzanej energii elektrycznej o charakterystyce niewypukłej - wykorzystanie metody optymalizacji roju czaogonekstek, 2013)
The main objective of economic load dispatch (ELD) is to allocate the output power generator at minimum cost while satisfying all the operation constraints. This paper presents a new hybrid method by integrating particle swarm optimization with time varying acceleration coefficients and evolutionary programming (TVAC-EPSO) for solving nonconvex ELD problem. The competition, sorting and selection in EP method are used to determine the best particle in PSO for finding the optimum solution efficiently. The proposed TVAC-EPSO has been tested on three different power system benchmarks. The simulation results have demonstrated the effectiveness of the proposed method in solving nonconvex ELD problem.